A numerical-experimental assessment on a composite fuselage barrel vertical drop test: Induced damage onset and evolution. (15th September 2020) - Riccio, A.; Saputo, S.; Sellitto, A.; Di Caprio, F.; Di Palma, L.
Abstract: Crashworthiness is the ability of a structure to withstand a crash event ensuring the safety of its passengers. The aim of this work is to investigate the damage onset and evolution in a composite fuselage barrel undergoing a vertical drop test on a rigid surface. The mechanical behaviour of the barrel has been assessed by means of a Numerical-Experimental study. Indeed, the experimental data from a full scale barrel test, performed at the CIRA facilities, have been used in conjunction with numerical results, obtained by means of an advanced 3D FEM model, to investigate, in detail, the deformations and the damage development during the crash event. The adopted three-dimensional numerical model, based on an explicit FE formulation, uses Continuum Shell elements and CDM to take into account the onset and the evolution of the intra-laminar damages in each subcomponent of the investigated composite fuselage barrel. The obtained numerical results have been compared with experimental data in terms of accelerations, displacements and deformations to provide a preliminary validation of the adopted FEM model. A special attention has been given to sub-components which demonstrated to mainly influence the global mechanical behaviour of the investigated composite fuselage barrel during the experimental test.